2000
DOI: 10.1152/ajpheart.2000.279.4.h1472
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2a-receptor activation increases contractility in isolated perfused hearts

Abstract: Adenosine A(2a)-receptor activation enhances shortening of isolated cardiomyocytes. In the present study the effect of A(2a)-receptor activation on the contractile performance of isolated rat hearts was investigated by recording left ventricular pressure (LVP) and the maximal rate of LVP development (+dP/dt(max)). With constant-pressure perfusion, adenosine caused concentration-dependent increases in LVP and +dP/dt(max), with detectable increases of 4.1 and 4.8% at 10(-6) M and maximal increases of 12.0 and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
61
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 36 publications
(50 reference statements)
10
61
1
2
Order By: Relevance
“…However, it is now shown that maximal velocities of Ca transient ratio increase and recovery are also increased upon A 2A R stimulation. The concentration of the A 2A R agonist CGS-21680 employed in this study is similar to the concentrations used in previous reports for perfused hearts (32,42) and ventricular myocytes (12,29). Although equilibrium-binding studies in the brain indicate that the inhibition constant K i for CGS-21680 is ϳ30 nM (21), generally higher concentrations of the agonist are required to observe a myocyte response within several minutes as performed above.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, it is now shown that maximal velocities of Ca transient ratio increase and recovery are also increased upon A 2A R stimulation. The concentration of the A 2A R agonist CGS-21680 employed in this study is similar to the concentrations used in previous reports for perfused hearts (32,42) and ventricular myocytes (12,29). Although equilibrium-binding studies in the brain indicate that the inhibition constant K i for CGS-21680 is ϳ30 nM (21), generally higher concentrations of the agonist are required to observe a myocyte response within several minutes as performed above.…”
Section: Discussionsupporting
confidence: 65%
“…This naturally occurring nucleoside in the myocardium (8,16) is capable of interacting with both the adenosine A 2A receptor (A 2A R) and adenosine A 1 receptor (A 1 R) to modulate contractile function. The A 2A R have been reported to increase contractile performance in rat (12) and neonatal avian (29) ventricular myocytes as well as increase the contractility of perfused rat (32) and mouse (42) hearts. A 2A R have been postulated to activate adenylyl cyclase (29) or initiate mechanisms that are Ca dependent and -independent (11,44) and cAMP independent (12,30).…”
mentioning
confidence: 99%
“…26 Because cardiac energy use appears to be downregulated in CHF, whereas adenosine production is increased, it is possible that adenosine may modulate metabolism in the failing heart through antiadrenergic effects on A 1 receptors or through inhibition of mitochondrial respiration via NO.…”
Section: Adenosine and The Failing Heartmentioning
confidence: 99%
“…Another conceivable mechanism whereby A 1 AdoR selective antagonism may increase cardiac output during hypoxia is allowing unopposed direct cardiac stimulation mediated by the A 2 AdoR (A 2a subtype). 17 Rapid, severe hypoxia is the primary problem in patients with certain insults (e.g., massive carbon monoxide exposure, near-drowning) and is a major contributing problem in others (e.g., acute airway obstruction, cardiac arrest). In these and in other lowflow states (e.g., hemorrhagic shock), impairments in systemic oxygenation or perfusion impair myocardial perfusion or oxygenation; endogenous Ado levels increase, presumably contributing to cardiac insufficiency.…”
Section: Resultsmentioning
confidence: 99%